THEMATIC-BASED STORY ILLUSTRATION PICTURE AS A CREATIVITY STIMULUS FOR THE FIRST-GRADE ELEMENTARY STUDENTS - Yofita Sari; Aldin Syahdan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
The abundance of emerging technologies in a civilization demands the readiness of the people as human resources to be more creative in all aspects. In terms of the research objectives, the researchers would like to develop a thematic-based story illustration picture as a creativity encouragement for first-grade elementary students. The research is a Research and Development (R&D) with the ADDIE model. The research sample is based on the purposive sampling technique. The sample consisted of 29 male students and 47 female students at the first-grade level. As a result, the average score in the pretest was 7.59. After applying to this program, it increased to 9.3 with an increase of 1.71. The minimum pretest score of 6.68 increased to 8.00, and the maximum post-test score of 8.50 initially increased to 9.8. It shows a significant increase in students' creativity. Based on the value of t-test = 9.01 with t-table (a = 0.05:110) at 1.658, there is a significant difference between the pretest and post-test scores. The research in this paper can be an appropriate innovation for the creativity program development for elementary students. It is because, in general, creativity programs are still theoretical and do not teach awareness and creative skills yet.Â .